Universiti Pertahanan Nasional Malaysia (UPNM) Way Forward: A Proposal of Cost Saving Strategy to Strengthen university Financial Through Saving Plan Package - Mohd Fadhzil Zainol (Journal of Human Development and Communication (JoHDeC), 2025)
This study aims to determine and propose appropriate recommendation to the top management of university on how to generate income through saving plan that can be implement by Human Resource Department at UPNM to strengthen the financial issue. This proposal is proposed to assist management team on how to rationalize limited financial issues that can affect financial crisis faced by the university nowadays. At present, all public universities in Malaysia faced a critical challenge due to insufficient financial budget allocation, where the Government’s financial allocation is increasingly bubbling. All Universities have been urged to generate their own internal income aside from budget allocation to ensure that the dependency on the Government can be reduce. Hence, some of these significant arrangements need to be carefully strategize and plan by the management of university to generate extra revenue as an effort to encounter financial issues faced by the university. From this case study, the finding can be used to identify and assist Top management of university to overcome issues on revenue generating to support financial operation cost at UPNM.